Zwei neue Aphiden aus dem Gebiet des Bezirkes Halle (Homoptera: Aphididae). - Müller, Fritz Paul (Contributions to Entomology = Beiträge zur Entomologie, 1968)
The rather black Aphis liliago sp. n. lives on the lower parts and on the inflorescences of Anthericum liliago Linnaeus. It has been found in nearly all the sites west and south of Halle in which the host plant occurs. The new species is extremely short haired. About 88 per cent OI the examined apterous viviparous females have ocelli on the vertex of the head. - The emerald-green Protaphis funicularis sp. n. settles on the root collar and the underside of the petioles of the lower leaves of its host plant Picris hieracioides Linnaeus. It is morphologically distingnished from the other members of the genus Protaphis Börner in that the processus terminalis is about 2 times as long as the base oi the ultimat,e antennal segment and the nnmber of the hairs on the cauda does not exceed 12.Nomenclatural Actsliliago Müller, 1968 (Aphis), spec. n.funicularis Müller, 1968 (Protaphis), spec. n.